Supervised mHeath Exercise Improves Health Factors More Than Self-Directed mHealth Exercise: A Clinical Controlled Study - Hu, Yukun; Zhang, Yong; Qi, XiaoYa; Xu, XiaoYang; Rahmani, Jamal; Bai, Ruixue; Mei, Ying (Frontiers in Public Health, 2022)
Wearable physical activity trackers are getting popular for self-management of weight despite the evidences are limited. Studies have proven that on-site supervised exercise is superior to unsupervised exercise to many health problems, there is no evidence comparing the effectiveness of remote supervision exercise with self directed exercise based on mHealth. The aim of this study is to compare the effects of mHealth based supervised exercise to mHealth based self-directed exercise on weight control in overweight and obesity population. A non-randomized controlled clinical study was conducted. Overweight or obesity volunteers were given personalized exercise prescriptions based on their HRR (Heart Rate Reserve), all patients were equipped with wearable heartbeat trackers to follow their exercise performance and additional remote supervisions were added to the intervention group. Exercise performances, weight losses and health examinations were compared between 2 groups after 12 weeks of follow-up. Analysis of covariance (ANCOVA) was used to determine any differences between study groups after intervention. Two groups had the same rate of attrition in 12 weeks follow-up, but the exercising day, the effective exercising day and the rate of effective exercising day in supervised group were higher than those in control group. Weight loss was-2.7±2.8kg in intervention group and-2.0±2.9kg in control group (P=0.23). Compared with control group, participants in intervention group improved their liver function, kidney function, Fasting blood sugar, Total cholesterol, and triglyceride. mHealth based supervised exercise is more effective in health factors improvement than mHealth based self-directed exercise among overweight and obesity participants.